Cloth masks as respiratory protections in the COVID-19 pandemic period: evidence gaps - Ana Cristina de Oliveira e Silva; Ana Maria de Almeida; Maria Eliane Moreira Freire; Jordana de Almeida Nogueira; Elucir Gir; Wynne Pereira Nogueira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to identify scientific evidence on the effectiveness of using cloth masks as safe protectors against COVID-19. Method: an integrative review of articles available in full obtained at PubMed, CINAHL, and Web of Science. Controlled, non-controlled descriptors and keywords such as "mask", "home-made" and "cloth" or "cotton" and "infection control" or "infection prevention" were used. Results: thirty-eight articles were selected; of these, seven studies made up the sample. Evidence shows that cloth masks do not have the same protective characteristics as surgical masks, indicating an increased risk of infection due to humidity, diffusion of fluids, virus retention, and improper preparation. Considering the shortage of surgical masks during the pandemic, cloth masks could be proposed as a last resort. Conclusion: cloth masks should be used together with preventive measures, such as home insulation, good respiratory conduct, and regular hand hygiene.